What makes a theme park experience less enjoyable? Evidence from online customer reviews of Disneyland China - Bai, Shizhen; He, Hao; Han, Chunjia; Yang, Mu; Bi, Xinrui; Fan, Weijia (Frontiers in Psychology, 2023)
This study aims to explore the causes of tourists’ less enjoyment in theme parks through an unsupervised machine learning approach – Structural Topic Modelling. Specifically, the research extracted a comprehensive list of discussion topics about their travel experience through the analysis of 112,000 customer reviews released by tourists from Shanghai Disney Resort from June 16, 2016 to March 4, 2022. Then, we use sentiment analysis to distinguish positive and negative topics, and explore the relationship between tourists who buy different ticket types and sentiment in negative topics. The results show that problems such as "parking", "service attitude", "recommendation feeling", "experience comparison" and "entrance" may be the main reasons for unpleasant experience. In addition, we also found that when tourists travel in groups (such as family tickets), customers feel unhappy because of parking problems and fast track problems. And when tourists travel alone or with small groups, staff's service attitude, experience comparison and entrance process are more concerned. Our findings can help theme park managers better understand the expectations of tourists, take effective measures to tackle issues causing customer dissatisfaction, and contribute to the theme park studies in tourism management.